PENGEMBANGAN BAHAN AJAR BAHASA ARAB BERBASIS MULTIMEDIA UNTUK PEROLEHAN BELAJAR AT-TA’ARUF SISWA KELAS X MAS AL-QOMAR MEMPWAH - Juharita, Juharita; Astuti, Indri; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract Based on the observations in Al Qomar Islamic Senior High School Mempawah, identified problem are (1) The Arabic language learning that have been implemented are still relying on the textbooks and students worksheet (LKS) as a learning resource; (2) the used strategies in learning Arabic language is still centered on the teacher (teacher center); (3) unavailability of multimedia-based Arabic learning teaching materials which can be used by the students independently in particular to train and improve the ability of speak, listen, read, and write the Arabic language. This study is a research development of multimedia-based teaching material products. The following steps of research are (1) preliminary studies (2) analysis of the learner needs (3) formulating content design and common components of learning (4) composing the flowchart and storyboard (5) designing and manufacturing the multimedia materials (6) validation from the experts (7) individual trials for 3 students (8) small group trials (6 students) (9) large group trials (13 students). Results of the validation by subject matter experts dan media experts conclude that the media feasible tested by the appropiate revision suggestions.The results showed the development of multimedia-based teaching materials for Arabic language for learning acquisition at ta’aruf can be used by the students easily and very pleasure, it also can be used independently anytime and everywhere. The learning activities that use this kind of multimedia can help the students to master the material completely and thoroughly as do the exercises repeatedly.Keywords: Development, Arabic language teaching materials, multimedia-based, the acquisition of learning at ta’aruf.